2012
DOI: 10.5114/wiitm.2011.31630
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided vacuum-assisted core biopsy in the diagnosis and treatment of focal lesions of the breast - own experience.

Abstract: IntroductionVacuum-assisted core biopsy (VACB) guided by ultrasound is a minimally invasive method used in diagnosis and treatment of breast focal lesions. Vacuum-assisted core biopsy is an interesting minimally invasive alternative to open surgical biopsy.AimTo assess the value of ultrasound-guided vacuum-assisted core biopsy in the diagnosis and treatment of breast focal lesions.Material and methodsIn the period 2009-2010, 397 ultrasound-guided vacuum-assisted core biopsies were performed. Mean age of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
(32 reference statements)
0
9
0
1
Order By: Relevance
“…It is clear that, although NLSB is considered the "gold standard," it is imperfect. If VASB can approach a false-negative rate as low as 1%-3%, as observed in the most recent studies (33), this modality should potentially replace NLSB for the first-line histopathological diagnosis of non-palpable mammographic lesions.…”
Section: Discussionmentioning
confidence: 85%
“…It is clear that, although NLSB is considered the "gold standard," it is imperfect. If VASB can approach a false-negative rate as low as 1%-3%, as observed in the most recent studies (33), this modality should potentially replace NLSB for the first-line histopathological diagnosis of non-palpable mammographic lesions.…”
Section: Discussionmentioning
confidence: 85%
“…[15][16][17][18] Among lesions with ultrasonographyehistologic discordance, 21.4% are upgraded in the pathological diagnosis after VAB, according to Li et al 19 Furthermore, it has also been reported that VAB might be valuable for definitive diagnosis when pathological results with CNB are discordant with imaging findings. [19][20][21] Accordingly, the use of VAB is supported by many physicians, especially for small lesions.…”
Section: Discussionmentioning
confidence: 94%
“…In recent years the vacuum-assisted core biopsy is increasingly common because it is an efficient and minimally invasive procedure to diagnose and treat focal lesions in the breast [ 12 ]. That is why Mondor's disease in patients who underwent this procedure may be observed more frequently.…”
Section: Discussionmentioning
confidence: 99%